Validation of the FASILA Score for Predicting Interventions and Outcomes in Traumatic Abdominal and Pelvic Injuries: A Prospective Clinical Study - Ayman El‐Menyar (17746911) (2025)
Background The FASILA score is a 7‐point scale comprising the FAST (focused assessment with sonography in trauma), shock index, and serum lactate. We aimed to validate this score prospectively in patients with abdominal and pelvic trauma to predict the need for massive blood transfusion, laparotomy, and inhospital mortality. Methods This prospective study included all adult patients who sustained abdominal and/or pelvic trauma. Pediatric patients, prehospital cardiac arrest, and severe head injury were excluded. Data were analyzed and compared with low (< 4) versus high (≥ 4) FASILA scores. Results A total of 400 patients (mean age 36.3 ± 12.7; 90% male; and 96% had blunt trauma) were enrolled between 2022 and 2024. Patients with higher FASILA scores (19.3%) had higher rates of exploratory laparotomy and radiological interventions and received more blood transfusions. They also had longer hospital stays, higher rates of sepsis, and mortality (p = 0.001). The FASILA scores significantly correlated with shock index (r = 0.75), ISS (r = 0.38), SOFA score (r = 0.36), and abdominal AIS (r = 0.27), TRISS (r = −0.19), RTS (r = −0.26), and fibrinogen levels (r = −0.12). A FASILA score ≥ 4 had a high specificity (85.5%) and negative predictive value (80%) for predicting the need for surgery. The FASILA score was an independent predictor of blood transfusion (odds ratio 1.92 and 95% CI 1.43–2.58) after adjusting for abdominal AIS, ISS, SOFA score, and fibrinogen level. AUROC curves were better for the FASILA score than ABC score and “SI alone” for the prediction of MTP and surgical interventions. Conclusion The significant association between high FASILA scores and blood transfusions, surgical interventions, and mortality indicates its usefulness in early risk stratification in abdominopelvic trauma. Multicenter studies are recommended to enhance external validity across diverse populations and settings. Other Information Published in: World Journal of Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/wjs.12632